Efforts to Improve Activities and Learning Outcomes of Volleyball Basic Techniques of Lower Passing Using The Drill Method - Sugito Sugito (Journal of Business, Social and Technology, 2022)
Research that focuses on teachers' efforts to increase activities and results. This study aims to improve volleyball bottom passing learning through the drill method for fifth graders at SD Negeri 2 Kalangan, Klego District, Boyolali Regency for the 2019/2020 Academic Year. This research is a Classroom Action Research (CAR). which consists of two cycles, each cycle consists of 1 meeting. The subjects of this study were the fifth grade students of SD Negeri 2 Kalangan, Klego District, Boyolali Regency, for the 2019/2020 academic year, with a total of 11 students. The instruments used for data collection in this study were the bottom passing assessment sheet, observation sheet for students and observation sheet for teachers. Groups for 2 cycles can improve student achievement. This can be proven from the results of observing student learning outcomes from 11 students in the initial conditions the number of students who achieved a KKM score of 70 was only 1 student, and in the first cycle increased to 6 students, then in the second cycle, increased to 11 students who achieved a KKM score of 70 even more. So that classical completeness in the class has more than 75% of students who have completed learning